Implementation of Scouting Values in Shaping Students' Nationalism Attitudes Through Sports Activities - Herman Herman; Charmila Tandi Rerung; Siti Nurhalizah Mutia Aulria (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This study aims to analyze the implementation of scouting values integrated with sports activities in shaping students' nationalism attitudes at SMA Negeri 6 Sinjai. Sports activities such as team sports, traditional games, and physical training are increasingly recognized as a powerful medium for character education and nationalism building. This research is a descriptive qualitative study with research subjects consisting of all members of the Scout extracurricular, totaling 26 students. Data collection was conducted through observation, interviews, and documentation in October 2025. The results showed that the integration of scouting values with sports activities including discipline, cooperation, leadership, fair play, and love for the homeland plays a crucial role in shaping students' nationalism attitudes. Scout activities combined with structured sports programs carried out regularly have a positive impact on understanding and practicing national values among students. The findings indicate that scouting values are reinforced through various structured activities including routine training, camping, exploration, social service, and sport-based games. These values significantly contribute to developing students' sense of patriotism, unity, and national responsibility.